SISTEM INFORMASI PELAYANAN UNIT JASA BERBASIS WEBSITE DENGAN CODEIGNITER PADA KOPERASI KARYAWAN SIT ALIYA - Muhammad Fakhri Mubarok Wasis Putra (2023)
The ALIYA Integrated Islamic School Employees Cooperative is an Employee Cooperative established by the ALIYA Group, located on Jalan Baru Bubulak, Bogor, to empower SIT ALIYA employees. Kopkar SIT ALIYA is considered to be quite advanced in the implementation of information technology. However, this cooperative faces issues in the management of service units, which still rely on Excel and manual, non-integrated forms. In this research, the researcher aims to design an information system website using CodeIgniter with the hope of assisting in data management, registration, payment, and reporting for the service units of Kopkar SIT ALIYA. The development method utilized is the prototype model. The developed service unit system for ALIYA Integrated Islamic School Cooperative is a system that supports features such as catering management, snacks, transportation, and monthly commissions, developed from February to July 2023.